The gap between here and there: Communication and information processes in the migration context of Syrian and Iraqi refugees on their way to Germany. (June 2019) - Fiedler, Anke
Set against the background of the so-called refugee crisis in Germany in 2015/16, this article asks about the subjective value that refugees give different sources of information and examines whether they were making informed decisions during the various stages of their transit. Between November 2015 and April 2016, four focus groups and 36 in-depth interviews were conducted with Syrian and Iraqi refugees, as well as interviews with Iraqi experts in the media and civil society sectors, based on the theoretical concepts of network and broadcast feedback developed by Bakewell and Jolivet. The results show that, unlike the mass media, personal network and narrowcast feedback were the most important sources of information for the study's participants. While most of the interviewees felt adequately informed both before and during their transit, it was mainly after the refugees arrived in Germany that they experienced a deficit of information.